Nois una estación inferopaleolítica en el área Cantabrico-Lucense - Ramil Rego, Eduardo (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This paper presents a new Lower Palaeolithic station located in the western area of the Cantabrian Sea. The lithic industry was in derived position and included within a soil horizon which laid on a marine terrace assigned to OIS 11. We studied the small lytic series consists of choppers, bifaces, cores and a flake; for their typological characteristics we can fit it into a not evolved Acheulean.